Trypanosoma cruzi antibodies in blood donors in Yucatan state, Mexico - García-Montalvo, Beatriz (Revista Médica del Instituto Mexicano del Seguro Social, 2018)
Background: blood transfusion is the second most frequent way of Trypanosoma cruzi (T. cruzi) transmission in Latin American countries. Few data exists on the geographic distribution and prevalence of T. cruzi seropositive blood donors in Mexico. The objective was to document T. cruzi antibody distribution, and identify the regions with the highest prevalence of seropositive blood donors.Methods: the analyzed data was collected over a six-year period during blood donations made at the Central Blood Bank and at the transfusion services and donation modules of the Instituto Mexicano del Seguro Social ( IMSS) located in the Yucatan state.Results: Trypanosoma cruzi antibody reactivity was determined in 86343 blood donors. Overall seroprevalence was 0.70 % (607/86 343). Since 2002 to 2004, the majority (58 %) of seropositive donors were rural residents, but since 2005 to 2007 the majority (56.6 %) were urban residents. The two highest seroprevalences by region were in the Metropolitan area (0.42 %) and in rural south Yucatan (0.09 %). Most seropositive donors resided in the municipality of Merida (60.3 %).Conclusions: seroprevalence distribution was heterogeneous during the study period but urban transmission has apparently surpassed rural transmission in recent years.